Understanding copyright law - Leaffer, Marshall A. (New Providence, NJ : LexisNexis, 2010)
Introduction to copyright and intellectual property law -- Subject matter of copyright : general standards -- Works of authorship : categories of copyrightable subject matter -- Publication, notice, and other formalities -- Ownership of copyright -- Duration, renewal, termination of transfers, and restoration of copyright -- Copyright registration and deposit -- The exclusive rights and their limitations -- Infringement and remedies -- Fair use and other defenses to copyright infringement -- Copyright law in a federal system : preemption of state law -- An overview of international copyright.
Includes bibliographical references and index.
BSBA
Keywords: Copyright --United States